Smoke and mirrors short fictions and illusions - Gaiman, Neil (New York, New York Avon Books, 1998)
A collection of fantasy stories and poems. In Chivalry, a woman discovers the Holy Grail in a secondhand shop, in Murder Mysteries, an angel visiting Los Angeles provides the inside story on Lucifer's revolt against God, and there are revisionist stories on Snow White and Santa Claus.
Reading the entrails: a rondel -- An introduction -- Chivalry -- Nicholas was ... -- The price -- Troll bridge -- Don't ask Jack -- The goldfish pool and other stories -- The white road -- Queen of knives -- Changes -- The daughter of owls -- Shoggoth's old peculiar -- Virus -- Looking for the girl -- Only the end of the world again -- Bay wolf -- We can get them for you wholesale -- One life, furnished in early Moorcock -- Cold colors -- The sweeper of dreams -- Foreign parts -- Vampire sestina -- Mouse -- The sea change -- When we went to see the end of the world by Dawnie Morningside, age 11 1/4 -- Desert wind -- Tastings -- Babycakes -- Murder mysteries -- Snow, glass, apples.